Problem solving skills of the nursing and midwifery students and influential factors - Nursan Çinar; Cefariye Sözeri; Sevil Şahin; Reyhan Cevahir; Mihriban Say (Universidade Federal de Goias, 2010)
Effective problem solving strategies and decision making skill based on a powerful basis of knowledge are behaviors expected from midwife and nurses students that need to be developed during their vocational education. This study aimed to determine and to compare the problem solving skills of nursing and midwifery students during their education and to verify the factors that influence the problem solving skills. The sampling comprised all the 252 students of the Midwifery and Nursing departments at School of Health Sciences of the University of Sakarya who volunteered for participating in the study and were present at school when data were collected (98 midwifery students and 154 nursing students). Data were collected using a questionnaire and "Problem Solving Scale" developed by Heppner and Petersen and the Turkish validity and reliability study was carried out by Sahin et al. The average problem solving scores were found to be 83.05±15.68 for the midwifery students and 86.85±18.55 for the nursing students. The midwifery students were found to be more successful than nursing students. It was also found that problem solving skills of inquisitive-extroverted students were better than that of the reserved ones.